Integrasi Nilai-nilai Islam dalam Pembentukan Karakter Siswa Melalui Pembelajaran IPA di Madrasah Ibtidaiyah - Rosita, Desyi; Fadillah Prabowo; Istiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the implementation of the integration of Islamic values in learning Natural Sciences (IPA) and its impact on the character building of grade V students in Madrasah Ibtidaiyah (MI). The method used is Classroom Action Research (PTK) with a qualitative approach. The research subjects consisted of 24 fifth grade students and a science teacher at MIN 2 Pandeglang, Pandeglang Regency, Banten. The research was conducted during the even semester of the 2024/2025 academic year, through two cycles of action with two meetings per week each. Data collection techniques included observation, interviews, student character questionnaires, and documentation, while data analysis was carried out descriptively qualitative and simple quantitative. The results showed that the integration of Islamic values in science learning significantly improved student character, from an average of 45.83% (pre-action) to 87.5% at the end of Cycle II. The most prominent improvement occurred in the aspects of gratitude, responsibility, honesty, social care, and discipline. These findings indicate that contextualised and religiously nuanced science learning is effective in shaping students' character, and is relevant as a reference in the development of an integrative curriculum in madrasah.